Quel(s) rapport(s) au marché du travail des élèves inscrits en Certificat d’Aptitude Professionnelle (CAP) ? - Claire Bonnard (Éducation et Socialisation)
While studies have shown that vocational education students have heterogeneous relationships with school, few have analysed their relationship with the labour market. This article proposes to study the link between the relationship to school and the labour market of students enrolled in a CAP. To this end, a survey was conducted among 750 students enrolled in a CAP through the school system and through apprenticeship. A typology made it possible to identify four student profiles that differ in their relationship to school and the labour market. The results underline that the relationship to school refers to different purposes and must be understood according to the value attributed to the diploma and the opportunities perceived by the student on the labour market. These different relationships will be constructed differently according to the student's gender, migration status, orientation and social and educational background.